Future-ready workforce agility in accounting profession: Input from Malaysian industry – A pilot study - Ahmad, Mahfuzah; Zainuddin, Zairul Nurshazana; Abdul Latif, Nurul Ezhawati; Mohamed Yusof, Faizal Mohamed; Alwi, Fatimah; Mahmud, Nurfarizan Mazhani (International Journal of Accounting, Finance and Business, 2026)
Workforce agility is the ability of employees to be flexible in a changing work environment. It is increasingly vital for Malaysian industries in facing technological and market shifts. This paper examines how digital proficiency, critical thinking, and organisational support contribute to workforce agility using Resource-Based View (RBV) theory. The data are collected from pilot survey in two Malaysian companies. The results indicate strong basic digital skills but only moderate critical thinking abilities, with Company A performing slightly better overall. The study stress key areas for improvement, especially in digital skills that boost efficiency and in advanced thinking skills. Then proposes a conceptual framework to guide organisational steps for strengthening future readiness.